Moving toward renewable energies: Mexico ́s Energetic Transition - Azuz-Adeath, Isaac; Cortés-Ruíz, Alejandra (My University, 2017)
Mexico has been historically among the main producers of oil and more recently of natural gas with a production in 2016 of 2.1 millions of barrels per day, and a volume of 54,000 million of cubic meters respectively, located in the twelfth and sixteenth place in the world ranking. The production tendencies between years 2004 and 2014, show a decrease of 28% concerning oil and inversely an increase of 43% in natural gas production. During the past three decades the energy policies have focused primarily in the exploitation of hydrocarbons thanks to the “oil boom” in Mexico, with the hydrocarbon ́s extraction, production, commercialization and distribution, and electrical energy generation and distribution, controlled by the state-owned Mexican Petroleum company (PEMEX) and the Federal Electricity Commission (CFE) respectively. On 2015, electric energy generation was distributed, according to the International Energy Agency (2017), as follows: natural gas (59.8%), coal (11%), oil (10.2), hydro (22.5%), nuclear (3.8%), geothermal (2%), wind (2.6%), biofuels and waste (0.5% and solar (0.1%). The global context and the necessity to broaden the commercial horizons concerning energetic policies, contributed to the creation and decree of several laws that promote the diversification of the energy generation sources in Mexico, of which must be mentioned: Law for the Use of Renewable Energy and the Financing of the Energetic Transition (2008), Law for the Sustainable Use of Energy (2008), Law on the Promotion and Development of Bioenergy (2008), General Law on Climate Change (2012), Geothermal Law (2014), Hydrocarbons Law (2014) and the Energy Transition Law (2015), among other. The purpose of this paper is to describe the current state of electrical energy generation in Mexico and the potential of development of renewable energy, taking into account the recent legal changes and implementation measures. The conclusions extracted of this analysis show the high potential for use renewable energy in the mexican territory.
Journal of International Area Studies
Keywords: Mexico; Energy; Energy transition; Renewable Energy; Energy Legislation